The Taguchi Approach in Optimizing Environmental Factors Affecting Productivity in the Automotive Industry - M. H. M., Haniff; Ahmad Rasdan, Ismail; B. M., Deros; M. N. A., Rahman; K., Kadirgama (Universiti Malaysia Pahang, 2011)
The objective of this study is to determine the dominance effects of environmental factors such as illuminance, humidity and WBGT on operators’ productivity in the Malaysian automotive industry. A case study was carried out at an automotive components assembly factory. The environmental factors examined were the illuminance (lux), humidity and WBGT of the surrounding workstation area. Two sets of representative data including the illuminance, humidity and WBGT level and production rate were collected during the study. The production rate data were collected through observations and survey questionnaires while the illuminance level was measured using photometer model RS 180-7133, and the humidity and WBGT level were measured by using Quest Temp apparatus and humidity. The Taguchi method was utilized to find the sequence of dominant factors that contributed to the productivity of the operator at that specified production workstation. The study reveals that the dominant factor that contributed to the productivity was humidity, followed by illuminance and WBGT.